SISTEM INFORMASI PENJUALAN BARANG DAN JASA PADA CV.HARYO JAYA MOBIL DI BLORA BERBASISI WEB (Information Technology and Telematics, 2016)
Abstract CV. Arya Jaya Mobil is one of the workshops that have services of good quality in the city Blora. CV. Haryo Jaya Mobil as a workshop that is quite famous in the city of Blora directly had an impact on revenues and number of subscribers. Problems of this research is how to make the information system sales of goods and services on a CV. Haryo Jaya Cars in Blora web based. The purpose of this research is to design and create a marketing system in the car repair workshop to facilitate penginformasian haryo jaya consumer data and earnings from the auto repair garage The tools of this study using the programming language PHP with MySQL as the database. Results of this research is expected to facilitate penginformasian consumer data, earnings data from the repair shop car repair services and marketing to more easily expand their market share and consumer interest. Conclusions and suggestions of this study to facilitate penginformasian kosumen of data, income data from the repair shop car repair services and marketing to more easily expand their market share and consumer interest as well as to optimize system performance and maximize function. Keywords: sales services, CV. Haryo Jaya, information systems